Nations as Strategic Players in Global Commodity Markets: Evidence from World Coal Trade - Moritz Paulus; Johannes Trüby; Christian Growitsch (Institute of Energy Economics at the University of Cologne (EWI), 2011)
We explore the hypothesis that export policies and trade patterns of national players in the steam coal market are consistent with non-competitive market behavior. We test this hypothesis by developing an equilibrium model which is able to model coal producing nations as strategic players. We explicitly account for integrated seaborne trade and domestic markets. The global steam coal market is simulated under several imperfect market structure setups. We find that trade and prices of a China - Indonesia duopoly fit the real market outcome best and that real Chinese export quotas in 2008 were consistent with simulated exports under a Cournot-Nash strategy.
Keywords: C61; F10; L13; L71; 330; Strategic National Trade; Imperfect Competition; Steam Coal; China; Indonesia